Dynamics of skyrmions and vortices in antiferromagnets - Harms, Joren (Student Undergraduate Research E-journal!, 2017)
Skyrmions are magnetic textures, that behave like particles. They exist as excitations within two-dimensional magnetic insulators and are promising candidates for future data storage. There has been a strong rise in interest in skyrmions in recent years, which is encouraged by several experimental observations of skyrmions in various magnetic thin-films. In this paper the classical dynamics of skyrmions and vortices in antiferromagnets are studied. We find that an antiferromagnetic skyrmion does not feel a Magnus force, while a ferromagnetic skyrmion does. We also see that an antiferromagnetic vortex feels a Magnus force.